Outcome and selection of revascularization strategy in left main coronary artery stenosis. (4th March 2018) - Gripenberg, Thomas; Jokhaji, Fadi; Östlund-Papadogeorgos, Nikolaos; Ekenbäck, Christina; Linder, Rikard; Samad, Bassem; Persson, Jonas
Abstract: Objectives. To investigate clinical outcome in unselected real-life patients with unprotected left main coronary artery (ULMCA) stenosis and determine factors associated with selection of revascularization strategy. Design. Consecutive patients with ULMCA stenosis at our institution in 2009–2013 ( n = 308) were retrospectively analyzed with propensity score adjusted Cox proportional hazards models for outcome. Baseline characteristics in relation to selection of revascularization strategy were analyzed with multivariate logistic regression. Results. Patients that underwent PCI ( n = 94) had a higher risk of major adverse cardiac and cerebrovascular events (MACCE; adjusted HR 2.13 [95% CI 1.08–4.19]) than patients that had CABG surgery but there was no difference in the combination of death and MI (adjusted HR 1.17 [95% CI 0.50–2.75]). Later year of index angiography, age, Euroscore II and angiographer favoring PCI was associated with PCI as revascularization strategy. Higher SYNTAX score, higher systolic blood pressure and angiographer favoring CABG was associated with CABG. Conclusions. In consecutive patients with ULMCA stenosis PCI is associated with higher MACCE rates than CABG but there is no difference in death and MI. Later year of index angiography, higher age, lower systolic blood pressure, higher predicted per-procedural surgical risk, less complex coronary anatomy and angiographer favoring PCI increased the probability of revascularization with PCI instead of CABG.